To Have a Need - Russ Colton (Ergo, An Open Access Journal of Philosophy)
Philosophers often identify needing something with requiring it to avoid harm. This view of need is roughly accurate, but no adequate analysis of the relevant sort of requirement has been given, and the relevant notion of harm has not been clarified. Further, the harm-avoidance picture must be broadened, because we also need what is required to reduce danger. I offer two analyses of need (one probabilistic) to address these shortcomings. The analyses are at a high level of generality and accommodate our ordinary notion of need as well as narrower conceptions. I also explain why the only extant, detailed modal account of need, David Wiggins’s (1987/1998), is inadequate. My analyses imply that to have a need for something is to have the (expected) quality of one’s life depend counterfactually on it in a certain way. The analyses shed some light on need’s distinctive normative significance.